Community Empowerment Through Creative Economic Entrepreneurship in Fish Farming in Pandeglang Regency - Eva Latifah; Pryo Handoko; Trisna Sonjaya; Ihin Solihin; Rizal Bahtiar (Jurnal Multidisiplin Sahombu, 2025)
This research aims to analyze community empowerment through the development of creative economic entrepreneurship based on fish farming in Pandeglang Regency. The method used is a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation of fish farmers and relevant institutions. The research results show that most people still practice fish farming conventionally and have not yet developed many creative and innovative aspects in their businesses. Nevertheless, various forms of creative economic enterprises have emerged, such as fish floss, fish skin crackers, and other processed products, which are largely driven by youth and women's groups. This business has proven capable of increasing community income and independence. However, its development still faces various constraints, such as limited capital, low entrepreneurial literacy, narrow market access, and suboptimal farmer institutions. Therefore, strategies that can be implemented include digital marketing and business management training, strengthening local branding, triple helix collaboration, business digitalization, and establishing a creative house for fishing villages. The conclusion of this study confirms that community empowerment through creative economic entrepreneurship in fish farming has great potential to be a solution for improving community welfare if supported by targeted, collaborative, and sustainable strategies.